Band-Structure Based model for photoelectron emission from metal surfaces - Rios, C.A. (2012)
Photoelectron emission spectra induced by grazing incidence of intense and ultrashort laser pulses on a metal surface are studied within a distorted-wave formalism. The proposed aproximation, named Band-Structure Based-Volkov (BSB-V) approach, includes a precise description of the surface potential, incorporating information of the band structure of the solid. Results are compared with the numerical solution of the time-dependent Schrodinger equation and with values derived from simpler theoretical models. © Published under licence by IOP Publishing Ltd.